PENERAPAN STRATEGI PENEMUAN TERBIMBINGUNTUK MENINGKATAN KEMAMPUAN KOGNITIF ANAK USIA 5-6 TAHUNDI TK AMAL IKHLAS RUMBAI PEKANBARU - Eliwarti Eliwarti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This research is motivated by low cognitive abilities of children in TK Amal Ikhlas Pekanbaru. It is known from: (1) low ability children in cognitive learning; (2) the child can not reveal what has been tried through trial activities; and (3) lack of memory of children in cognitive learning. It required an application of concrete to be able to find the right way with respect to the child's cognitive ability, namely the application of guided discovery strategy. The formulation can study the researchers formulated as follows: Does the use of guided discovery strategy can improve the cognitive abilities of children aged 5-6 years in TK Amal Ikhlas Pekanbaru ?. This study aims to determine whether the use of guided discovery strategy can improve the cognitive abilities of children aged 5-6 years in TK Amal Ikhlas Pekanbaru. The method used in this research is classroom action research (classroom action research) with a number of research subjects as many as 20 children, consisting of 12 boys and 8 girls. Data collection techniques of data collection in this study is the observation and documentation. Data analysis techniques used in this study is the percentage technique. Results of action research a cognitive ability of children increased from the initial data is known that cognitive ability 31.3. In the first cycle of the first meeting of 39.3. In the first cycle of the second meeting of 48.5. In the second cycle the first meeting of 56.3. And the second cycle II meeting of 67.8. Based on these results we concluded that the results of this study with the application of guided discovery strategy can improve the cognitive abilities of children aged 5-6 years in TK Amal Ikhlas Pekanbaru. The percentage increase cognitive abilities of children aged 5-6 years at the age of 5-6 years with the implementation strategy guided discovery at TK Amal Ikhlas Pekanbaru can be seen from prasiklus or before the implementation of the strategy of guided discovery to the second cycle.